ANALISIS PAJAK, UKURAN PERUSAHAAN, PROFITABILITAS, LEVERAGE, KEPEMILIKAN ASING DAN TUNNELING INCENTIVE TERHADAP TRANSFER PRICING (Studi Kasus Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2014 – 2018) - Nur Afifah; Heni Agustina (PROSIDING NATIONAL CONFERENCE FOR UMMAH, 2020)
aims to determine the effect of taxes, company size, profitability, leverage, foreign ownership and tunneling incentives on transfer pricing in manufacturing companies listed on the Indonesia Stock Exchange. The sample used consists of 13 manufacturing companies from 2014 to 2018, using a targeted sampling method. The data analysis in this research is descriptive statistics, classic hypothesis testing, multiple regression analysis and hypothesis testing. Based on the results of this study it shows that between 2014 and 2018, company size and foreign ownership have a positive and significant effect on transfer pricing, then leverage and tunneling incentives have a negative effect on transfer pricing, and taxes and profitability have no effect on transfer pricing. At the same time, taxes, company size, profitability, leverage, foreign ownership, tunneling incentives affect transfer pricing.